Efficacy and toxicity evaluation of celastrol in adjuvant-induced arthritis rat model - Sousa, Ânia Robim Costa e (2017)
Rheumatoid Arthritis (RA) is a chronic systemic autoimmune inflammatory disease that mainly affects the joints, and is characterized by active inflammation as well as bone and cartilage destruction. Since structural joint damage is irreversible, early recognition and treatment are currently being emphasized, with the goal of inducing remission of the disease. Current RA therapies fail or produce only partial responses in most patients and have adverse toxicological effects, so there is still an unmet need for a drug that can offer an effective and safe treatment of RA. Celastrol, is a compound extracted from an herb used in Chinese medicine, which was previously identified by our work group as a potential candidate for the development of a new therapeutical drug for inflammatory diseases, such as RA. Therefore, the main goal of this project was to evaluate the efficacy and toxicity of the oral administration of a range of Celastrol dosages, using an adjuvant-induced arthritis (AIA) rat model. In order to achieve this, we treated AIA rats with dosages of Celastrol of 1 μg/g, 2.5 μg/g, 12.5 μg/g and 25 μg/g, from day 8 post disease induction until day 22, when rats where sacrificed. Blood and paw samples were collected for quantification of bone turnover and degradation serum markers, histological and immunohistochemical evaluation, as well as for quantification of toxicological blood parameters. Our work showed that an orally administered dosage of 2.5 μg/g of celastrol in the rat AIA model effectively reduces inflammation, infiltration and proliferation of synovial cells, suppresses bone erosion, reduces the number of osteoclasts and osteoblasts and reduces the number of synovial CD68+ cells, thus suggesting this treatment as effective. Moreover, we also showed that this treatment has no adverse toxicological effects at dosages of 1 μg/g and 2.5 μg/g, and that dosages of 25 μg/g and 12.5 μg/g can be considered lethal dose (LD) and LD50, respectively.